A randomized, prospective comparison of transition to sirolimus‐based CNI‐minimization or withdrawal in African American kidney transplant recipients. Issue 5 (14th March 2016) - Fleming, James N.; Taber, David J.; Pilch, Nicole A.; McGillicuddy, John W.; Srinivas, Titte R.; Baliga, Prabhakar K.; Chavin, Kenneth D.; Bratton, Charles F.
Abstract: Background: There is a lack of conclusive evidence to suggest if calcineurin inhibitor (CNI) withdrawal or minimization with sirolimus is the best strategy for African Americans. Methods: This was a randomized, prospective, open‐label, pilot study comparing the two mammalian target of rapamycin (mTOR) transition strategies in adult African Americans between six and 24 wk post‐transplant. The primary outcome was a comparison of the eGFR at one yr after conversion. Results: Forty patients were randomized and analyzed in an intent‐to‐treat fashion. Median day of transition was day 96 (withdrawal) and 68 (minimization). Patients in the CNI‐withdrawal group (n = 23) had significantly higher eGFR at one yr compared to the CNI‐minimization group (n = 17, 73 vs. 56 mL/min, p = 0.03), as well as a significantly larger increase in eGFR from baseline (12 vs. 5 mL/min, p = 0.03). There were no differences in infections, acute rejection, death, or graft loss. Both regimens were constrained by disproportionately high discontinuation rates despite modest toxicity profiles. Conclusion: In spite of considerable withdrawal rate across both study arms, African American kidney transplant recipients who underwent early transition to a sirolimus‐based CNI‐withdrawal regimen had significantly better graft function at one yr compared to those transitioned to a sirolimus‐based CNI‐minimization regimen. Clinicaltrials.gov identifier: NCT01005706.